Developing and deploying non- and low-sweet sweetpotato cultivars for expanding markets - Carey, E.E.; Swanckaert, J.; Dery, E.; Akansake, D.; Saaka, J.; Abidin, P.E.; Adofo, K.; Baafi, E.; Muzhingi, T.; David, M.; Low, Jan W.; Grüneberg, W.J. (International Society for Horticultural Science, 2019)
A major objective of breeding at the Sweetpotato Support Platform for West Africa in Ghana, is the development of non-sweet cultivars suitable for use as staple foods, or in fried and other processed products. This priority was set during stakeholder consultations when establishing the program, and is based on the opinion that sweetness constrains the potential for greater uptake and enhanced value-addition of sweetpotato in West Africa. Similar efforts are underway at the International Potato Center’s headquarters in Lima, Peru. Moreover, studies indicate that urban consumers in many countries are increasingly health conscious and are seeking out products with low sugar contents. Initial breeding efforts in Ghana focused on adaptation to the lowland tropical West African environments where sweetpotato virus disease pressure is high and rains can be uncertain. Populations include a range of flesh colors, including β-carotene-rich orange-fleshed, anthocyanin-rich purple-fleshed, and yellow- and white-fleshed genotypes, with generally high dry matter content (>30%). Consumer sensory panels conducted at the village level consistently rate the majority of advanced selections highly with respect to texture, taste, aroma and appearance, though these contain varying levels of sugars and perceived sweetness. Recent and current efforts focus on better characterizing non- and low-sweet selections, and developing strategies for their dissemination, particularly through urban market segments. Sugar content in cooked or processed sweetpotato is influenced by various factors, including the sugar content prior to cooking, the method of cooking, and the levels of amylase activity during cooking, which can significantly increase maltose levels. Storage interval can significantly influence sugar content and amylase activity. Elite, non-sweet genotypes with low or null β-amylase activity are present among released cultivars and advanced selections in Ghana, and have excellent quality both in steamed and fried forms. Marketing research efforts build on previous successful experiences promoting and marketing the orange-fleshed sweetpotato, and include branding these new quality types with a distinct name.